Ultrasonographic, Surgical, and Histopathological Findings of a Uterine Leiomyoma in a Cow. (18th March 2012) - Sharma, Arvind; Kumar, Adarsh; Imran, Sheikh; Sood, Pankaj; Asrani, Rajesh Kumar
Abstract : The objective of this case report was to describe the ultrasonographic, surgical, and histopathological findings of a rare clinical case of uterine leiomyoma in a 5-year-old Holstein crossbred cow presented for diagnosis and treatment of infertility. Transrectal palpation revealed a large nonpainful mass suspected to be an abscess or a tumor in the caudal abdomen on the right side. Transabdominal ultrasonography revealed a round mass with irregular hypoechogenic/echogenic foci and a thin echogenic capsule around it. Ultrasonographic-guided centesis of the lesion under local analgesia did not yield any foul smelling aspirate leading to a tentative diagnosis of an intra-abdominal tumor. The lesion was later confirmed by exploratory laparotomy and histopathology as a case of uterine leiomyoma. The cow gave birth to a live normal calf 12 months following the surgery. Rectal examination after parturition revealed no evidence of the tumor at the surgical site. Ultrasonography enabled prompt, noninvasive diagnosis of uterine leiomyoma and proved to be a useful decision-making tool in the abdominal surgery of the cow. This is an interesting case which broadens the spectrum of the causes of infertility in cattle.